ANALISIS KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI DENGAN PENDEKATAN FUNDAMENTAL : STUDI KASUS PADA EMITEN SEKTOR TELEKOMUNIKASI - Anggriani, Putri Bunga; Maulidya, Maulidya; Mayada, Mayada; Muliyani, Muliyani (STIE Atma Bhakti, 2025)
This study aims to analyze the financial performance of PT Telkom Indonesia (Persero) Tbk (TLKM) and compare it with other listed telecommunication companies in Indonesia using a fundamental analysis approach. The research highlights key issues related to financial health assessment from the dimensions of profitability, liquidity, solvency, and market valuation. The study employs a quantitative-descriptive method based on secondary data collected from annual financial reports and the Indonesia Stock Exchange. Financial ratios such as ROA, ROE, NPM, CR, DER, PER, and PBV are used as indicators. The results show that TLKM maintains a strong and stable financial structure with consistent profitability and moderate leverage. Despite the decline in market valuation metrics, the company remains fundamentally healthy compared to its peers. In contrast, competitors like MORA, LINK, DATA, and INET display varying financial characteristics, with some exhibiting high profitability but risky capital structures. These findings suggest that TLKM presents a relatively lower risk profile for medium-to-long-term investors and may serve as a benchmark for assessing competitiveness in the Indonesian telecommunications sector. This study provides practical insights for investors, analysts, and policymakers to make more informed decisions in evaluating listed telecommunication firms in emerging markets like Indonesia.